A genome-wide association study finds genetic variants associated with neck or shoulder pain in UK Biobank. (3rd April 2020) - Meng, Weihua; Chan, Brian W; Harris, Cameron; Freidin, Maxim B; Hebert, Harry L; Adams, Mark J; Campbell, Archie; Hayward, Caroline; Zheng, Hua; Zhang, Xianwei; Colvin, Lesley A; Hales, Tim G; et al.
Abstract: Background: Common types of musculoskeletal conditions include pain in the neck and shoulder areas. This study seeks to identify the genetic variants associated with neck or shoulder pain based on a genome-wide association approach using 203 309 subjects from the UK Biobank cohort and look for replication evidence from the Generation Scotland: Scottish Family Health Study (GS:SFHS) and TwinsUK. Methods: A genome-wide association study was performed adjusting for age, sex, BMI and nine population principal components. Significant and independent genetic variants were then sent to GS:SFHS and TwinsUK for replication. Results: We identified three genetic loci that were associated with neck or shoulder pain in the UK Biobank samples. The most significant locus was in an intergenic region in chromosome 17, rs12453010, having P  = 1.66 × 10 −11 . The second most significant locus was located in the FOXP2 gene in chromosome 7 with P  = 2.38 × 10 −10 for rs34291892. The third locus was located in the LINC01572 gene in chromosome 16 with P  = 4.50 × 10 −8 for rs62053992. In the replication stage, among four significant and independent genetic variants, rs2049604 in the FOXP2 gene and rs62053992 in the LINC01572 gene were weakly replicated in GS:SFHS ( P =  0.0240 and P  = 0.0202, respectively). Conclusions: We have identified three loci associated with neck or shoulder pain in the UK Biobank cohort, two of which were weakly supported in a replication cohort. Further evidence is needed to confirm their roles in neck or shoulder pain.